2018
DOI: 10.3390/molecules23123352
|View full text |Cite
|
Sign up to set email alerts
|

Fermentability of a Novel Galacto-Oligosaccharide Mixture by Lactobacillus spp. and Bifidobacterium spp.

Abstract: This study aimed to investigate the specific growth stimulation of certain desired intestinal bacteria by a novel galacto-oligosaccharide mixture, which was produced with a β-galactosidase from a potential probiotic Lactobacillus isolate that contained mainly oligosaccharides of β-1,3 and β-1,6 glycosidic linkages (termed Lb-GOS) using single-strain fermentations. The composition of this Lb-GOS mixture was 33.5% disaccharides, 60.5% trisaccharides, 4.8% tetrasaccharides, and 1.0% pentasaccharides with a neglig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 47 publications
3
24
0
Order By: Relevance
“…[49]. In addition, different species of Lactobacillus harbor β-galactosidases that enable them to grow fast on GOS [50]. The abundance of Lactobacillus has been reported to directly relate to positive self-judgment, through which it is indirectly related to cognitive depression and reduced cognitive empathy [51].…”
Section: Discussionmentioning
confidence: 99%
“…[49]. In addition, different species of Lactobacillus harbor β-galactosidases that enable them to grow fast on GOS [50]. The abundance of Lactobacillus has been reported to directly relate to positive self-judgment, through which it is indirectly related to cognitive depression and reduced cognitive empathy [51].…”
Section: Discussionmentioning
confidence: 99%
“…Strain maintenance used the conditions slightly modified from the literature. 34 Briefly, Bifidobacterium spp. and lactobacilli were maintained at −72 °C in MRS (de Man, Rogosa, and Sharpe) broth containing 0.5 g/L l -cysteine hydrochloride and 15% (w/v) glycerol.…”
Section: Methodsmentioning
confidence: 99%
“…31,37 In the case of potential probiotic bacteria, it has been reported that bifidobacteria such as B. bifidum NCIMB 41171 synthesize GOS formed mainly with β-(1 → 3) linkages, 38 P. acidipropionici LET 120 produces GOS β(1 → 6), β(1 → 3) and β(1 → 4) linked trisaccharides, 21 whereas other Lactobacillus species have been shown to produce β-(1 → 6) and β-(1 → 3) linkages in their transgalactosylation mode. 25,29,39 This property is relevant since we have recently studied the digestibility of these compounds using brush border membrane vesicles from pig small intestine and found that β(1 → 6) linkage had higher resistance than β(1 → 4) and β(1 → 3) linkages. 40 Therefore, the new synthetized GOS could be expected to reach the gut in large quantities.…”
Section: Synthesis Of Oligosaccharides From Lactose and Lactulosementioning
confidence: 99%
“…have shown the ability to use the trisaccharides derived from lactulose and lactose, but with a general preference towards β(1 → 6) and β(1 → 3) over β(1 → 4) linked products. 35,39,41 Then, it could be expected that CRL450-GOS/ OsLu could exhibit good prebiotic potential. Table 2 shows the concentration of oligosaccharides (di-, tri-and tetrasaccharides) obtained with CRL450-β-gal from both substrates.…”
Section: Synthesis Of Oligosaccharides From Lactose and Lactulosementioning
confidence: 99%